Ingested a fish bone-induced ileal perforation: A case report. Issue 15 (April 2020) - Song, Junchuan; Yang, Weijin; Zhu, Yuewen; Fang, Yongchao; Qiu, Jiandong; Qiu, Jianshen; Lin, Lan; Wu, Weihang; Lin, Chen; Wang, Yu
Abstract: Introduction: Gastrointestinal perforation due to foreign body intake is rare and often secondary to unintentional intake; hence, a misdiagnosis is likely. Herein, we report a case of perforation of the ileum due to fish bone. Case presentation: A 57-year-old woman presented with right lower abdominal pain. She did not provide any information about having a history of swallowing foreign bodies. Surgery for uterine fibroids and subtotal gastrectomy was performed 6 years ago. Diagnosis: Laboratory tests and imaging examination showed normal results. During laparotomy, a fish bone was found at the end of the ileum. Two senior radiologists re-evaluated the computed tomography scan, and confirmed the presence of the suspected foreign body. Interventions: Partial intestinal resection and manual ileum end anastomosis were performed. Outcomes: The patient recovered well after surgery and recalled that she had eaten fish the night before experiencing abdominal pain. Conclusion: An accurate diagnosis of complications due to fish bone intake, often secondary to the unintentional intake, is quite challenging. Detailed history-taking about the patient's diet and eating habits is therefore important. Clinical manifestations are mainly determined by the location of perforation, which typically occurs at the junction of the ileum and rectal sigmoid colon. Imaging examination and surgery are often used for definite diagnosis.